Non-Linear Effects of Tax Changes on Output : The Role of the Initial Level of Taxation - Gunter, Samara; Riera-Crichton, Daniel; Vegh, Carlos; Vuletin, Guillermo (World Bank, Washington, DC, 2018)
This paper estimates the effect of worldwide tax changes on output following the narrative approach developed for the United States by Romer and Romer (2010). The analysis uses a novel dataset on value-added taxes for 51 countries (21 industrial and 30 developing) for the period 1970-2014 to identify 96 tax changes. It then uses contemporaneous economic records to classify such changes as endogenous or exogenous to current (or prospective) economic conditions. In line with theoretical distortionary and disincentive-based arguments, and using only exogenous tax changes, the main finding is that the effect of tax changes on output is highly non-linear. The tax multiplier is essentially zero under relatively low/moderate initial tax rate levels and more negative as the initial tax rate and the size of the change in the tax rate increase. Based on a global sample, these novel non-linear findings suggest that the recent consensus pointing to large negative tax multipliers in industrial countries, particularly in Europe (e.g., Alesina, Favero, and Giavazzi, 2015), (i) is not a robust empirical regularity, and (ii) is mainly driven by high initial tax rates in these countries. The paper also shows that the bias introduced by misidentification of tax shocks critically depends on the procyclical or countercyclical nature of endogenous tax changes. The relevance of the arguments is evaluated both for the novel global sample and for Romer and Romer's U.S. dataset.